Use of Topical 5-Fluorouracil for Keratocystic Odontogenic Tumors of Gorlin-Goltz Syndrome as a New Targeted Therapy: A Case Report and Review of Literature - hossein shiran; SH Shafaei Fard; S Hakimi; A Azari Pour Esfahani (Islamic Azad University, 2019)
Background: Keratocystic odontogenic tumors (KOT) have a high rate of recurrence, which is higher in patients diagnosed with Gorlin-Goltz syndrome (GGS). Adjunctive therapies, such as fixative chemical solutions, decrease the rate of recurrence after enucleation and peripheral ostectomy but have high morbidity rates. Topical 5-Fluorouracil (5-FU) has been suggested as a new therapy that provides a directed molecular approach to treatment. Case Presentation: This is a case report of GGS treated using topical 5-FU as an adjunctive material after enucleation and peripheral ostectomy. New bone formation sites were identified in the radiographic follow-up. The patient was followed up for 10 months regularly without any evidence of recurrence. Conclusion: 5-FlU is an effective and novel targeted treatment for KOTs. Topical application of 5-FU, following enucleation and peripheral ostectomy, effectively treats syndromic KOTs, resulting in normal bony healing with no adverse local or systemic effects.